(untitled) (Research, Society and Development, 2021)
This study aims to verify in the literature the scientific evidence on the role of nurses in the prevention of ventilator-associated pneumonia (VAP), with a search for articles in the Virtual Health Library, covering studies published between 2015 and 2019. of nurses to direct assistance to the prevention of infection related to mechanical ventilation through risk prevention interventions. The databases consulted for the research were: VHL; BDENF; SCIELO. As inclusion criteria, articles published in Portuguese were adopted, available in full between the years 2015 to 2019. The study showed that VAP can have serious repercussions for the patient affected by this condition and has a great impact on morbidity and mortality rates, in the time on MV, in the length of stay in the ICU. Therefore, it is essential to select and apply evidence-based measures, appropriate for each health service and according to the individual needs of patients, since such measures, when applied collectively, have been proven to reduce the incidence density of VAP , one of the most frequent infections related to health care in ICUs, in this context, nurses play a fundamental role in care, together with the care team, in the prevention of infection, and must be able to perform the most complex activities, supported by scientific knowledge. implemented from the daily practice of caring and research, in order to conduct care with self-confidence and security.